2011
DOI: 10.1371/journal.pone.0024785
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Poultry House Environment on Poultry Litter Bacterial Community Composition

Abstract: Viral and bacterial pathogens are a significant economic concern to the US broiler industry and the ecological epicenter for poultry pathogens is the mixture of bedding material, chicken excrement and feathers that comprises the litter of a poultry house. This study used high-throughput sequencing to assess the richness and diversity of poultry litter bacterial communities, and to look for connections between these communities and the environmental characteristics of a poultry house including its history of ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(77 citation statements)
references
References 82 publications
3
71
2
1
Order By: Relevance
“…Other studies utilizing both PCR and culture confirmation have been able to identify Arcobacter in a large percentage of chicken intestines, though the rates of detection vary significantly between flocks . Arcobacter has also been identified in poultry house litter at high levels, but was not ubiquitous across all houses (Dumas et al, 2011), consistent with other reports of sporadic detection in chicken feces.…”
Section: Poultrysupporting
confidence: 89%
“…Other studies utilizing both PCR and culture confirmation have been able to identify Arcobacter in a large percentage of chicken intestines, though the rates of detection vary significantly between flocks . Arcobacter has also been identified in poultry house litter at high levels, but was not ubiquitous across all houses (Dumas et al, 2011), consistent with other reports of sporadic detection in chicken feces.…”
Section: Poultrysupporting
confidence: 89%
“…In farms A and H, some drinking nipples were contaminated with Salmonella. Previous studies have indicated that moist environments promote the multiplication of microflora (Rusin et al, 1998), and bacterial abundance on wet litter was found to more diverse than that in dry conditions (Dumas et al, 2011). Furthermore, the absence of dry cleaning between laying rounds reportedly worsens the Salmonella contamination status in conventional battery cages (Van Hoorebeke et al, 2010).…”
Section: Eric-pcr Fingerprinting and Clustering Analysismentioning
confidence: 95%
“…The environment in the production system can be a potential source of infections and the severity and outbreaks of the diseases are directly related to the level of contamination of the environment (DUMAS et al, 2011). According to Sesti (2005), the adoption of an effective biosecurity program is the best alternative to maintain commercial flocks free or controlled from the presence of diseases of economic impact in productivity or dangerous to public health.…”
Section: Resultsmentioning
confidence: 99%